34.3k views
4 votes
5x – 2 (2x - 1) = 2 (3x-4)

1 Answer

3 votes

Answer:

x = 2

Explanation:

5x - 2 ( 2x - 1 ) = 2 ( 3x - 4 )

First we need to distribute from the parenthesis.

5x -4x + 2 = 6x -8

Now look for any numeral that can be added or subtracted that is on the same side, here for example is 5x and -4x.

x + 2 = 6x - 8

Now find the side with the larger x value, and either add or subtract the lingering number on that side, ours here is 8.

x + 2 = 6x - 8

+8 +8

x + 10 = 6x

Near our last few stages subtract or add the smallest value x from the largest.

x + 10 = 6x

-x -x

10 = 5x

Finally, we divide each side by the number next to x.

10 = 5x

10/5 =2

5x/5 = x

To put our eqaution in correct form we write

x = 2

Hope this helps :)

User Life Evader
by
6.2k points